Perancangan Motif Khas Tasikmalaya Pada Decoupage Untuk Produk Dari Anyaman Pandan - Imamul Masyhudi; Kresnawan Budiargo (Universitas Multimedia Nusantara, 2021)
Tasikmalaya woven is able to penetrate the export market in three countries; Japan, Italy and Spain. In the midst of the rapid development of this product, there are problems, the development of image motifs that are less varied. The decoupage drawing technique is more attractive to consumers than the manual hand drawing technique. The design of this decoupage motif uses a three-step methodology; exploration, design and embodiment. In the design, it was found that many distinctive motifs could be extracted from Tasikmalaya, for example flora, fauna, nature and culture motifs. The purpose of this design is to give a distinctive motif to the woven product so that it has the uniqueness and identity of Tasikmalaya. Keywords: woven; decoupage; distinctive motifs; export product